DON’T LET IT GO! Saving endangered plants through seed storage - Chin, H. F. (UTAR Agriculture Science Journal, 2016)
Many species and varieties of plants are at risk of extinction. Seed banks offer a way to conserve their seeds as frozen assets for the future.